PENDIDIKAN DALAM PERSPEKTIF URHANUDDIN AL-ISLAM AZ-ZARNUJI - Waris, Waris (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: Big Moslem scholar who live in town of Zarnuj regional of Iraq, now this Afganistan have complete name of Burhanuddin Al-Islam Az-Zarnuji. He live during with Ridha Ad-Din An-Naisaburi between year 500-600 H, while pass awaying him there is telling year 591 H besides year 593 H. Education concept told by Az-Zarnuji by monumental poured in his masterpiece of TaâLimul MutaâAllim. According to that education he cover five factor that is target of education, educated (student), educator (teacher), appliance (medium) education and environment. While education which is have Islam nuance to. in the masterpiece discussed in 13 section. which by he concluded into three big shares. that is division of science, target and intention learn, and also study method.Â ØªØ§ÙÙØ§ÙÙØ§ ÙØ¯ØØ§ Ø¬ÙÙØ±Ø² Ø©ÙÙØ¯Ù ÙÙ ÙÙØ³Ù ØÙØ¬ÙÙØ±Ø²ÙØ§ ÙÙØ§Ø³ÙØ¥Ø§ ÙÙØ¯ÙØ§ ÙØ§ÙØ±Ø¨ ÙÙ ÙØ¬ÙÙØ±Ø²ÙØ§ ÙØ§ÙÙØ¥Ù ÙÙØ§ÙÙØ§ ÙØ³ÙØ§Ø§Â ÙÙ600 - 500 Ø©ÙØ³ÙØ§ ÙÙØ§Ø® ÙØ±ÙØ¨Ø§Ø³ÙÙÙØ§ ÙÙØ¯ÙØ§ ÙØ¶Ø± ÙÙØ§Ø¹ÙØ§ ÙÙ Ø±ØµØ§Ø¹Ù .ÙØ§ØªØ³ÙØ§ØºÙØ£ ÙÙ ÙÙØ¢Ø§ Ø¹ÙØªÙ ØÙØ§Ø±Ø¹ÙØ§ ÙÙÂ . â ÙÙ ÙØ¹ØªÙÙØ§ ÙÙÙØ¹Øª â ÙÙØ±Ø¹ÙÙØ§ ÙØ¨Ø§ØªÙ ÙÙ Ø©ÙØ¨ØªØ±ÙØ§ ÙØ¹ ÙÙÙÙØ§ÙÙÙ ÙØ±Ø§ÙÙØ£ ÙÙ Ø¯Ù .ÙÙ 593 Ø©ÙØ³ ÙÙÙÙ ÙÙ591 Ø©ÙØ³ ÙÙÙØªÙÂ Ø³Ù Ø±Ø¯ÙÙØ§ )3 ØØ¨ÙØ§Ø·ÙØ§ )2 ØØ©ÙØ¨ØªØ±ÙØ§ ÙØ§Ø¯ÙØ£ )1 : Ø±ØµØ§ÙØ¹ Ø©Ø³Ø®Ù ÙÙØ¹ ØªÙÙØªØ´Ø§ Ø©ÙØ¨ØªØ±ÙØ§ ÙØ£ ÙØ¬ÙÙØ±Ø²ÙØ§ ÙØ§ÙÙØ¥Ø§ ÙØ£Ø±Â ÙÙ Ø©Ø±ÙÙØ°ÙÙ â ÙÙ ÙØ¹ØªÙÙØ§ ÙÙÙØ¹Øª Ø¨Ø§ØªÙ ÙÙ â Ø©ÙÙÙØ§Ø³ÙØ¥Ø§ Ø©ÙØ¨ØªØ±ÙØ§ ØªØ§Ø¹ÙØ¶ÙÙ Ø§ÙØ£ .Ø©Ø¦ÙØ¨ÙØ§ )5 ØÙØ¦Ø§Ø³ÙÙØ§ )4 ØÙÙ ÙØ¹ÙÙØ§ ÙØ£.ÙÙÙØ¹ØªÙØ§ ÙØ±Ø·Ù ØÙÙØ¹ØªÙØ§ Ø§ÙØ§ÙÙÙ ÙØ§Ø¯ÙØ£Ù ØÙÙØ¹ÙØ§ ÙØ§Ø³ÙØ£ ÙÙ ØØ¨Ø§ÙØ¨Ø£ 3 ÙÙ ÙÙØ¤ÙÙØ§ Ø§ÙØµÙØ®ØªØ³Ø§ Ø ÙØ§ØµÙ 13